Vloga prostorskega planiranja v gospodarskem in regionanem planiranju - Ravbar, Marjan (Geographica Slovenica, 2000)
Regarding its intention, regional policy is representing the basic instrument for the long-term and accordant direction of spatial and regional development and represents the stage of agreement reached in connection with basic problems and aims of direction of regional development on the level of the state, landscapes and communities. Regional policy is forming the framework for striving for market economic effectiveness, social justice and ecological acceptability of development, which is to respect the legal regime of the state, cultural originality of the nation and living interests of all inhabitants. It stipulated basic regulations for formation of regional plans and adoption of developmental decisions.
Keywords: prostorsko planiranje; spatial planning; regionalno planiranje; regionalni razvoj; regije; ekonomski razvoj; Slovenia; Slovenija